An Assessment of Heavy Metals Soil Pollution and Health Risk Around Industrial District in Qayarah Area, Northern Iraq (Iraqi National Journal of Earth Science (INJES), 2024)
QR1>AB5>AB4>QF8>AB3>AB2>GS4>QF7>QR2>QF9.Whereas, the enrichment and pollution factors for heavy elements followed the following order: As>Ni>Cd>Cr>Pb>Co. The values of the total carcinogenicity factor through ingestion, dermal contact, and inhalation were (1.2x10-4), (6.91x10-4), and (7.85x10-3) respectively, all exposure pathways to studied pollutants are in the following order : Carcinogenic inhalation hazard > Carcinogenic skin hazard > Carcinogenic oral hazard. Site AB6 is considered the most polluted due to the impact of most influential factors and a high probability of cancer risk.]]>
Keywords: Qayarah,,; ,،Pollution,,; ,،Heavy metals,,; ,،Health risk,,; ,،Industrial district